2006
DOI: 10.1016/j.jvs.2006.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus surgical treatment of venous leg ulcers: A prospective, randomized, multicenter trial

Abstract: In conclusion, we suggest that patients with medial and/or recurrent ulceration should receive surgery combined with ambulatory compression therapy. A dedicated center should provide care for those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 12 publications
1
113
1
4
Order By: Relevance
“…Since its first description by Hauer in the 1980s, 1) SEPS has been accepted as an improved treatment modality in the surgical treatment of perforating vein insufficiency, particularly in cases with advanced skin changes. SEPS is performed in some facilities in North America [2][3][4][5] and Europe [6][7][8][9][10] as a component of the comprehensive treatment program for venous insufficiency. These previous studies presented favorable results with SEPS.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description by Hauer in the 1980s, 1) SEPS has been accepted as an improved treatment modality in the surgical treatment of perforating vein insufficiency, particularly in cases with advanced skin changes. SEPS is performed in some facilities in North America [2][3][4][5] and Europe [6][7][8][9][10] as a component of the comprehensive treatment program for venous insufficiency. These previous studies presented favorable results with SEPS.…”
Section: Introductionmentioning
confidence: 99%
“…The data for RRs were based on a systematic review of RCTs7, which are usually considered to be the most valid form of evidence. At the time of publication of the systematic review7, the ESCHAR RCT21 reported substantially fewer recurrences after surgery at 4 years, whereas van Gent and co‐workers31 showed no difference in recurrence at 2 years. However, recently published long‐term follow‐up from the latter study showed that surgery almost halved the probability of recurrence at 10 years32, corroborating the outcome of the ESCHAR trial21.…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate Cox regression analysis previous vein surgery was the only factor significantly associated with recurrent ulceration (p=.004) 26 . SEPS combined with superficial venous surgery leads to healing with a low recurrence rate in patients with open and healed venous ulcers [24][25][26][27][28] Rejection of clip(after one month) through port site sinus 2 % …”
Section: Discussionmentioning
confidence: 99%